Dynamic Scenarios in Two-State Quantum Dot Lasers Excited State Lasing, Ground State Quenching, and Dual-Mode Operation - Röhm, André; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2015)
André Röhm investigates the dynamic properties of two-state lasing quantum dot lasers, with a focus on ground state quenching. With a novel semi-analytical approach, different quenching mechanisms are discussed in an unified framework and verified with numerical simulations. The known results and experimental findings are reproduced and parameter dependencies are systematically studied. Additionally, the turn-on dynamics and modulation response curves of two-state lasing devices are presented. Contents Quantum Dot Laser Theory Two-State Lasing and Ground-State Quenching Modulation Response Target Groups Researchers and students in the field of theoretical physics Practitioners in this area The Author André Röhm wrote his master’s thesis under the supervision of Prof. Dr. Eckehard Schöll, PhD and Prof. Dr. Kathy Lüdge in the Collaborative Research Center SFB 910 at the Institute of Theoretical Physics at TU Berlin.
Quantum Dot Laser Theory -- Two-State Lasing and Ground-State Quenching -- Modulation Response.             .
Keywords: Mathematical physics; Atoms; Physics; Optical materials; Electronic materials; Theoretical, Mathematical and Computational Physics; Atomic, Molecular, Optical and Plasma Physics; Optical and Electronic Materials